Postoperative exercise training is associated with reduced respiratory infection rates and early discharge: A case-control study. Issue 3 (June 2017) - Bhatt, N.R.; Sheridan, G.; Connolly, M.; Kelly, S.; Gillis, A.; Conlon, K.C.; Lane, S.; Shanahan, E.; Ridgway, P.F.
Abstract: Introduction: Pulmonary complications are a significant cause of morbidity, mortality and increased hospital stay following complex abdominal surgery. We investigated whether postoperative early aerobic activity with a pedal exerciser reduced respiratory morbidity and length of stay and improved pulmonary function. Methods: A prospective case-control study on 30 cases and 30 case matched controls aged 18 years or more who underwent major surgery was conducted. Controls were case-mix matched prospectively from a similar general surgical service not utilising postoperative exercising. Thirty consecutive cases were started on a twice-daily aerobic exercise program with pedal exerciser post-operatively day 2 or from when sitting independently. Primary outcome measures were respiratory tract infection (RTI), deep vein thrombosis (DVT) or pulmonary embolus (PE). Secondary outcome measure was subjective breathlessness and Length of Stay (LOS) postoperatively. Results: The rate of RTI was only 16.6% in the exercise group and 43.3% in the control group (P = 0.024). None of the cases or controls suffered from a DVT or PE. Median postoperative length of stay in the control group was 11 ± 7.5 days whereas in the cases it was 8.5 ± 5.00 days (P = 0.049). The Borg subjective breathlessness score in the cases group showed a decline in the subjective breathlessness on postoperative day 4 (P = 0.002). Conclusions: Early aerobic activity with a pedal exerciser halves the rate of postoperative RTI and postoperative hospital stay after complex abdominal surgery. Subjective breathlessness was also reduced with the use of pedal exerciser, signifying potential to improve exercise endurance in the postoperative patient.